2015
DOI: 10.1007/s00299-015-1842-5
|View full text |Cite
|
Sign up to set email alerts
|

Xanthones from roots, hairy roots and cell suspension cultures of selected Hypericum species and their antifungal activity against Candida albicans

Abstract: Highest xanthone contents were found in Hypericum pulchrum and H. annulatum untransformed roots. The best anti- Candida activity was obtained for hairy roots extracts of H. tetrapterum clone 2 ATCC 15834. Extracts of root cultures, hairy roots and cell suspensions of selected Hypericum spp. were screened for the presence of xanthones and tested for their antifungal activity against Candida albicans strain ATCC 10231. At least one of the following xanthones, 5-methoxy-2-deprenylrheediaxanthone; 1,3,6,7-tetrahyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 38 publications
(47 reference statements)
4
27
1
1
Order By: Relevance
“…Unlike hypericins, hyperforins, and flavonoids, which occur in the aerial parts of H. perforatum plants, xanthones are abundant in the roots, albeit their content fluctuates as a result of genetic variation and environmental factors (Crockett et al, 2011;Li et al, 2013;Tocci et al, 2013b;Zubrick a et al, 2015). In hairy roots, which result from Agrobacterium rhizogenes transformation, the xanthone concentration was increased compared with that in untransformed roots (Tusevski et al, 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…Unlike hypericins, hyperforins, and flavonoids, which occur in the aerial parts of H. perforatum plants, xanthones are abundant in the roots, albeit their content fluctuates as a result of genetic variation and environmental factors (Crockett et al, 2011;Li et al, 2013;Tocci et al, 2013b;Zubrick a et al, 2015). In hairy roots, which result from Agrobacterium rhizogenes transformation, the xanthone concentration was increased compared with that in untransformed roots (Tusevski et al, 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…Another study reported that JA treatment significantly increased phenolic compounds, flavanols and flavonols, concomitantly reducing the anthocyanin content . A twofold increase in the xanthone, cadensin G and paxanthone contents was found in cell suspension cultures of H. perforatum following elicitation with SA …”
Section: Manipulation Of Hypericum Perforatum Secondary Metabolism VImentioning
confidence: 96%
“…[70] These authors also reported that treating H. perforatum shoot cultures with a S. maltophilia culture filtrate induced only pseudohypericin production. [70] Analysis of the methanolic extract of cell suspension cultures treated with A. tumefaciens revealed a 12-fold increase in the total xanthone concentration and the emergence of [41] Iron nano-oxide Hypericin and hyperforin [41] Chitin Phenolics, flavonols, flavanols, anthocyanins, hypericin and pseudohypericin [66] Pectin Phenolics, flavonols, flavanols, anthocyanins, hypericin and pseudohypericin [66] Dextran Phenolics, flavonols, flavanols, anthocyanins, hypericin and pseudohypericin [66] Phytophthora cinnamoni fungal cell wall extract None [39] Colletotrichum gloeosporioides mycelium extract Xanthones and flavonoids [35] Aspergillus flavus mycelium extract Phenolic compounds, flavanols, flavonols, anthocyanins and hypericins [62] Fusarium oxysporum Phenolics, flavonoids, anthocyanins, hypericin and pseudohypericin [63] Phoma exigua Phenolics, flavonoids, anthocyanins, hypericin and pseudohypericin [63] Botrytis cinerea Phenolics, flavonoids, anthocyanins, hypericin and pseudohypericin [63] JA Hypericins [39] JA Phenolic compounds, flavanols, flavonols, hypericin and pseudohypericin [38] MeJA Flavones [35] MeJA Flavonoids [8] SA Xanthones [85] SA None [35] SA None [39] SA Hypericins, pseudohypericins [86] SA Flavonoids [8] MeJA + C. gloeosporioides Xanthones [35] SA + C. gloeosporioides Xanthones [35] Agrobacterium tumefaciens Xanthones [71] A. tumefaciens Lignin and flavanoids [72] A. tumefaciens Phenolics, flavonols, flavanols and xanthones [73] A. rhizogenes Phenolics, flavonols, flavanols and xanthones [73] Callus SA Hypericins, pseudohypericins [86] Root MeJA Hypericin [84] IBA Hypericin [84] Acetic acid Xanthones…”
Section: Fungi and Extracts From Fungal Myceliamentioning
confidence: 99%
See 1 more Smart Citation
“…Os resultados da atividade antifúngica frente às leveduras C. (SINGH et al, 2011;ZUBRICKÁ et al, 2015, MOKOKA et al, 2013MONTAGNER et al, 2008 A banda de absorbância em 230nm poderia ser atribuída aos flavonoides, já que os taninos condensados são formados por unidades de flavan-3-ol (uma classe de flavonoides).…”
Section: Análises Dos Ensaios Antifúngicos Frente Aos Fungos Candida unclassified